A hybrid method for damage detection and condition assessment of hinge joints in hollow slab bridges using physical models and vision-based measurements. (15th January 2023) - Hu, Hao; Wang, Jiji; Dong, Chuan-Zhi; Chen, Jiaqi; Wang, Tao
Abstract: The simply supported slab bridge is a typical perfricated reinforced concrete bridge. Under the influence of increasing vehicle loads and natural environmental erosion, the hinge joints between slabs suffer from damage that cannot be easily evaluated, which brings negative effects on the load carrying capacity of bridges. In the present study, a hybrid method for damage detection and condition assessment of hinge joints in hollow slab bridges using physical models and vision-based measurements was proposed. The stiffness reduction of hinge joints is taken as the damage degree and condition level of the inspected hinge joints. An analytical model of a simplified spring-mass system was firstly built to demonstrate the applicability of using the relative displacement ratio as the damage index of hinge joints. The relationship between the relative displacement ratio and the stiffness reduction of hinge joints was then studied thoroughly through a parametric study on finite element models considering different damage levels of hinge joints. Thresholds of the relative displacement ratio were defined to classify the damage states of hinge joints. The damage index of target hinge joints can be calculated from the actual data provided by using computer vision-based multi-camera and multi-point displacement measurements. Lastly, the application of a real-life bridge under normal traffic was demonstrated to verify the feasibility of the quantitative evaluation of the service status of joints in hinged-slab bridges. It indicated that the proposed method could evaluate the damage degree of joints quantitatively, effectively and economically.